Croatia: Reality of Labor Protection – At the Crossroads of Individual and Collective Labor Law - Vinković, Mario (Fundamentals of Labor Law in Central Europe, 2022)
The chapter is focused on understanding collective agreements and collective bargaining in the Republicof Croatia, as well as the relationship between individual employment contracts and collective agreements through both theoretical and dogmatic approaches to the subject matter. The data on the coverage of workers by collective agreements is intended to provide insight into the reality of the application and scope of collective agreements, but also to highlight the risks of the part of the population in the labor market that does not benefit from their direct or indirect protection. According to available data, more than 50% of workers in the Republic of Croatia are covered by collective agreements. However, the insufficiently reliable records and the fact that there is still no comprehensive national register of all concluded and valid collective agreements are problematic. Special attention is paid both to the open issues de lege lata and to the phenomena that have characterized the development of Croatian labor law from the independence of the state to the recent events during the pandemic COVID-19 and the announced adoption of the new Labor Act, the fourth in the last twenty-seven years. Since in the process of transformation of employment relationships and fragmentation of the labor market certain institutions of labor law become particularly important, the legitimate question arises not only about the influence of trade unions on the relevant processes, but also about their ability to assert themselves as generators of social dialogue focused on vulnerable groups of workers and consolidation of membership. The author has tried to avoid a purely normative analysis and focus on the sociolegal discourse and methodological pluralism in terms of content structure and approach. Keywords: collective agreement, collective bargaining, employment contract, labor law